2017
DOI: 10.1061/(asce)hy.1943-7900.0001224
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Description on the Role of Turbulence and Grain Interference on Particle Entrainment from Gravel Beds

Abstract: 4A complete understanding of the role of grain-scale particle-flow interaction in sediment 5 entrainment and transport has still not been achieved in spite of recent technological advancement 6 in measurement capabilities. In this study the initial motion of natural sediment particles in a gravel 7 deposit was detected and combined with simultaneous local measurements of the velocities on a 8 horizontal plane located above the bed surface using a three-component stereoscopic PIV. A series of 9 experimental tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…A minimum resting time t min = 0.10 s was selected based on previous findings by Nelson et al (), reporting high correlations between entrainment events and near‐bed streamwise velocities measured approximately up to 0.10 s before transport occurred in weakly mobile beds. Similar observations (from tests B1 to B6 in this study) were later confirmed by Cecchetto et al (), who found that most particles were entrained by bursting events with duration of 0.05 to 0.1 s This value provides mean duration of normalized bursting events, Tutrue¯max/H (with T = t min the duration of the bursting event, utrue¯max the surface water velocity, and H the water depth), in the range 1.0 to 3.0, in agreement with earlier observations by Nikora and Goring (), Nezu and Nakagawa (), and Dey et al ().…”
Section: Methodology: Reconstruction Of Particle Trajectoriessupporting
confidence: 92%
See 2 more Smart Citations
“…A minimum resting time t min = 0.10 s was selected based on previous findings by Nelson et al (), reporting high correlations between entrainment events and near‐bed streamwise velocities measured approximately up to 0.10 s before transport occurred in weakly mobile beds. Similar observations (from tests B1 to B6 in this study) were later confirmed by Cecchetto et al (), who found that most particles were entrained by bursting events with duration of 0.05 to 0.1 s This value provides mean duration of normalized bursting events, Tutrue¯max/H (with T = t min the duration of the bursting event, utrue¯max the surface water velocity, and H the water depth), in the range 1.0 to 3.0, in agreement with earlier observations by Nikora and Goring (), Nezu and Nakagawa (), and Dey et al ().…”
Section: Methodology: Reconstruction Of Particle Trajectoriessupporting
confidence: 92%
“…This enabled a population sample of ~800–900 individual particles composing the surface layer of the investigation area to be observed at each recording time. In total 12 tests were carried out with increasing bed shear stress and constant water depth h u = 100 mm (more details are in Tregnaghi, Tregnaghi, Bottacin‐Busolin, Tait, et al, and Cecchetto et al, ). Following Schmeeckle and Nelson (), in the selected tests B1 to B6 (Table ) the ratio between the Shields parameter and the critical Shields parameter, τ */ τ * cr , ranged from 1.15 (low transport stage) to 1.70 (moderate transport stage), where τ * cr = 0.053 is calculated with the reformulated Shields' expression reported in van Rijn's ().…”
Section: Experimental Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…e 1-1 area and 2-2 area (shown as Figure 9) are the same, so α 1 is approximately equivalent to α 2 . From the continuity equation of uid mechanics [22], it can be known that there is a relationship between the volume ux Q of 1-1 and 2-2 cross-sectional area as follows:…”
Section: E Building Of Computing Methodmentioning
confidence: 99%
“…erefore, an all-purpose computing method was proposed for quicksand through the borehole in this paper. e Bernoulli formula [22], Darcy-Weisbach formula [17], semiempirical Nikuradse formula [23,24], and Colebrook-White formula [25,26] were combined to calculate the volume ux of quicksand. Besides, the volume concentration, density, and viscosity of sand-water mixture were tested for the method used in similar engineering.…”
Section: Introductionmentioning
confidence: 99%